2008
DOI: 10.3168/jds.2007-0537
|View full text |Cite
|
Sign up to set email alerts
|

Effect of In Vitro Docosahexaenoic Acid Supplementation to Marine Algae-Adapted and Unadapted Rumen Inoculum on the Biohydrogenation of Unsaturated Fatty Acids in Freeze-Dried Grass

Abstract: The objective of this study was to examine the ruminal biohydrogenation of linoleic (18:2n-6) and linolenic (18:3n-3) acid during in vitro incubations with rumen inoculum from dairy cattle adapted or not to marine algae and with or without additional in vitro docosahexaenoic acid (DHA, 22:6n-3) supplementation. Treatments were incubated in 100-mL flasks containing 400 mg of freeze-dried grass, 5 mL of strained ruminal fluid, and 20 mL of phosphate buffer. Ruminal fluid was collected just before the morning fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
18
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 30 publications
6
18
0
2
Order By: Relevance
“…Shingfield et al (2008) showed that milk from cows fed diets supplemented with sunflower oils, with a high level of LA, linearly increased OBCFA levels (iso C15:0, C15:0 and anteiso C17:0) compared with milk from the unsupplemented group. The same results occurred in vitro, where bacterial synthesis of OBCFA increased with DHA supplement feeding level (Vlaeminck et al, 2008).…”
Section: Odd and Branched Chain Fatty Acids: A New Frontier In The Stsupporting
confidence: 68%
“…Shingfield et al (2008) showed that milk from cows fed diets supplemented with sunflower oils, with a high level of LA, linearly increased OBCFA levels (iso C15:0, C15:0 and anteiso C17:0) compared with milk from the unsupplemented group. The same results occurred in vitro, where bacterial synthesis of OBCFA increased with DHA supplement feeding level (Vlaeminck et al, 2008).…”
Section: Odd and Branched Chain Fatty Acids: A New Frontier In The Stsupporting
confidence: 68%
“…The increase in propionate and the decrease in butyrate concentrations with the FO diet were also reported in other studies Lee et al, 2008;Vlaeminck et al, 2008) with the use of FO or algae. These changes may be linked to the alterations in the bacterial community seen in this study with the FO diet (discussed below).…”
supporting
confidence: 63%
“…However, this later octadecatrienoic isomer was not detected in our samples. The 18∶2 trans -11, trans -15 have been previously reported in milk [50], omasal digesta [45], rumen fluid [51], lamb meat [52] and beef [53], and it is also associated with dietary intakes of 18∶3n−3. The occurrence of the 18∶2 cis -9, cis -15 and cis -12, cis -15 in lamb meat was already described by our group [46], furthermore these BI were proposed to be products of the ruminal biohydrogenation of the 18∶3n−3, resulting from the reduction of the cis -12 or cis -9 double bonds, respectively.…”
Section: Discussionmentioning
confidence: 76%